The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1681/asn.2015040346
|View full text |Cite
|
Sign up to set email alerts
|

Renal Therapeutic Angiogenesis Using a Bioengineered Polymer-Stabilized Vascular Endothelial Growth Factor Construct

Abstract: Renovascular disease (RVD) induces renal microvascular (MV) rarefaction that drives progressive kidney injury. In previous studies, we showed that renal vascular endothelial growth factor (VEGF) therapy attenuated MV damage, but did not resolve renal injury at practical clinical doses. To increase the bioavailability of VEGF, we developed a biopolymer-stabilized elastin-like polypeptide (ELP)-VEGF fusion protein and determined its in vivo potential for therapeutic renal angiogenesis in RVD using an established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
104
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 50 publications
11
104
0
1
Order By: Relevance
“…In collaboration with Dr. Chade, we tested the ELP-VEGF fusion protein’s ability to reverse vascular damage and improve renal function in the swine RVD model. We found that when administered intrarenally six weeks after induction of renal artery stenosis, ELP-VEGF was mostly retained in the injected kidney with some spillover into the contralateral kidney, and it significantly improved renal function and increased microvascular density in the stenotic kidney (47). Importantly, ELP-VEGF outperformed free VEGF in its ability to induce improved renal function, indicating that fusion to the stabilizing biopolymer is beneficial.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In collaboration with Dr. Chade, we tested the ELP-VEGF fusion protein’s ability to reverse vascular damage and improve renal function in the swine RVD model. We found that when administered intrarenally six weeks after induction of renal artery stenosis, ELP-VEGF was mostly retained in the injected kidney with some spillover into the contralateral kidney, and it significantly improved renal function and increased microvascular density in the stenotic kidney (47). Importantly, ELP-VEGF outperformed free VEGF in its ability to induce improved renal function, indicating that fusion to the stabilizing biopolymer is beneficial.…”
Section: Introductionmentioning
confidence: 97%
“…In a series of studies using a swine model of renal artery stenosis (4143), Chade et al have implicated VEGF deficiency and resulting microvascular loss in the deterioration of renal function. Renal artery stenosis induced by placement of a local irritant coil lead to progressive deterioration of renal function over the course of several weeks that was accompanied by reduced renal VEGF expression (43).…”
Section: Introductionmentioning
confidence: 99%
“…However, a potential limitation of this approach is that exogenously administered growth factors possesses a brief plasma half‐life and are prone to degradation 39. This limitation can be overcome by fusion of growth factors with a biopolymer synthetic protein based on human elastin 40, 41. Elastin‐like polypeptide (ELP) is composed of a repeating 5 amino acid motif that is thermally responsive,25, 41, 42 facilitating purification of ELP and ELP‐fusion proteins by thermal cycling 43.…”
mentioning
confidence: 99%
“…The renal endothelium lacks regenerative capacity early after IRI, unlike the tubule epithelium, potentially due to a low level of angiogenic signals and endothelial proliferation[2,12]. Approaches to preserve the renal endothelium such as infusion of VEGF in pigs after established renovascular disease, prevented microvascular rarefaction, attenuated fibrosis & normalized renal blood flow and kidney function compared to controls[13], suggesting that targeting therapeutic interventions to promote endothelial function may be an effective strategy to reduce fibrosis.…”
Section: Role Of Endothelium In Pathophysiology Of Renal Fibrosismentioning
confidence: 99%
“…Blockade of prosurvival factors such as VEGFR2 or PDGFRβ has been shown to reduce pericyte proliferation and differentiation, microvascular rarefaction, inflammation and fibrosis[16]. The apparent discrepancy between these findings and that administration of VEGF protects against fibrosis [13] may be due to the complex signaling pathway including three VEGF receptors and the regulated expression of four distinct VEGF genes and multiple splice variants. Therefore, these studies cannot simply be explained by a binary ligand receptor interaction .…”
Section: Role Of Endothelium In Pathophysiology Of Renal Fibrosismentioning
confidence: 99%